[en] The aesthetic experience about of Aylan Kurdi: the perversion that surrounds us - Amaral, M. E. P. [UNESP]; Bertolli Filho, C. [UNESP] (Univ Complutense Madrid, Servicio Publicaciones, 2018)
The proposal of this article is to analyze the reception of the images that portrayed the death in the Syrian boy Aylan Kurdi in 2015. Through the aesthetic experience, as methodology of data collection, and the culture circuit, idealized by Richard Johsnon, the research looks to recognize perverse movements in the reception of these objects in a focal group performed among brazilians living in Aveiro, Portugal.
Keywords: Circuit; Aesthetic experience; Perversion